Odpowiedź :
-(4-x)+2(x+1)=5+x
-4+x+2x+2=5+x
-4+2x+2=5
-2+2x=5
2x=5+2
2x=7 /:2
x= 7/2=3 1/2
x/4-5=2x/3+1
3x-60=8x+12
3x-8x=12+60
-5x=72 /:-5
x=72/5=14 2/5
1/2(x-2)=x/2+1
x-2=x+2
-2=2
x€0
Działanie nie może być spełnione ponieważ nie ma wartości x
Odpowiedź:
-(4-x)+2(x+1)=5+x
- 4+x+2x+2=5+x
3x - x=5+2
2x=7 /:2
x=3,5
spr
- (4 - 3,5)+2*(3,5+1)=5+3,5
- 0,5+2*4,5=8,5
- 0,5+9=8,5
8,5=8,5
x/4-5=2x/3+1
1/4x - 2/3x=1+5
3/12x - 8/12x=6
- 5/12x=6 /*( - 12/5)
x= - 14,4
spr
1/4*( - 14,4) - 5=2/3*( - 14,4)+1
- 3,6 - 5= - 9,6+1
- 8,6= - 8,6
1/2(x-2)=x/2+1
1/2x - 1=1/2x+1
1/2x - 1/2x=1+1
0≠2 równanie sprzeczne
Szczegółowe wyjaśnienie: